Climbing Research Initiative: Movement & Performance Labs. The science of climbing at your fingertips (2021)
CRIMP Labs is dedicated to the science of climbing. Our mission is to support you in connecting with the phenomena you experience while climbing. We believe that a better understanding in the science of why will empower you to become more effective in achieving your training and climbing goals. We trust that understanding diverse topics in climbing science can inspire us all to become better stewards and advocates for our sport.